Beneficial Effect of Rosuvastatin Therapy on Spleen Injury Induced by Gamma Irradiation in Rats: Targeting Nrf2/EPRE Pathway - Thanaa M. Fahim; Marwa Abd EL-Hameed Mohamed; Sahar S. M. Abdelrahman; Dina M. Lotfy (SAGE Publishing, 2023)
Purpose The present study investigates the new approach of rosuvastatin (RUV) administration as a drug for the management of spleen injury induced by gamma irradiation. Main Methods Forty rats were used and divided equally into 4 groups: control group, irradiated group, IRR + rosuvastatin group (10 mg/Kg b. wt), and IRR + rosuvastatin group (20 mg/kg b. wt) for 7 days orally. Results The possible curative effect can be illustrated via the improvement of hematopoietic cell count (Hb, RBCs, and WBCs) and oxidative stress markers (MDA and GST) in addition to biochemical parameters including [heme oxigenase-1 (HO-1), nuclear erythroid 2-related factor (Nrf2), NOD-, LRR- and pyrin domain- containing protein 3 (NLRP3) inflammasome] and immune assay of nuclear factor kappa beta (NF-kB P65) and inducible nitric oxide synthase (iNOS). Histological pictures emphasize the biochemical findings. Rosuvastatin treatments by using two different doses improve the tested parameters. High-dose administration of RUV (20 mg/kg p.o.) recorded better results than the low dose (10 mg/kg p.o.). Conclusion Our results suggested that rosuvastatin reversed the radiation-induced spleen-damaging effects. So, RUV can be introduced to the market as a new therapy for the management of spleen damages.